A Canadian Perspective on Addiction Treatment. Issue 3 (July 2014) - el-Guebaly, Nady
This paper presents a synopsis of addiction treatment in Canada, along with some available comparative figures with other North American countries. Within the framework of Canada's Medicare, a largely single-payer system, addiction and psychiatric disorders are insured on par with other medical disorders. Canada's strategy recognizes the four pillars of prevention, treatment, harm reduction, and enforcement. The Canadian Alcohol and Drug Use Monitoring Survey is the yearly main source of data on alcohol and illicit drug use. The main features of the Canadian addiction treatment network are identified as a "top 10" list, outlining early identification and intervention, assessment, and referral; detoxification; ambulatory care/day treatment programs; residential care; hospitals; concurrent disorders networks and regionalization; drug specific strategies; mutual help; behavioral addictions; and training, qualification, and research.